The Effect of Nurses’ Therapeutic Communication on People with Schizophrenia: A Literature Review - Rikhan Luhur Prasetya; Febi Septiani (Jurnal EduHealth, 2026)
Schizophrenia significantly impairs psychological functioning, behaviour, and social interaction, necessitating comprehensive nursing interventions. Therapeutic communication is considered a core nursing competency in establishing effective therapeutic relationships and optimising patient outcomes. This scoping review aimed to synthesise recent evidence on the effects of nurses’ therapeutic communication in the care of patients with schizophrenia. A scoping review was conducted following the Arksey and O’Malley framework. Literature searches were performed in PubMed, Google Scholar, ScienceDirect, and Garuda for primary studies published between 2019 and 2025 using the keywords “therapeutic communication,” “nurse,” and “schizophrenia.” Ten eligible studies employing quantitative, qualitative, or mixed-methods designs were analysed through thematic mapping. The findings consistently demonstrate that therapeutic communication contributes to measurable improvements in patient outcomes, including enhanced self-concept, reduced anxiety and anger, decreased aggressive behaviour, improved hallucination control, and strengthened therapeutic alliance. These results reinforce the role of structured, empathy-based communication strategies as an evidence-informed intervention in psychiatric nursing practice. Overall, integrating therapeutic communication into schizophrenia care supports more effective management across multiple psychiatric nursing diagnoses and strengthens the therapeutic process, highlighting its strategic value in improving clinical and psychosocial outcomes.